EFFORTS TO IMPROVE THE TANK CLEANING PROCESS TO SUPPORT THE FAST LOADING OF FUEL OIL IN MT. SUCCESS MARLINA XXXIII - Suhartini Suhartini; April Gunawan; Rizky Muhammad Adhiwirayuda (Dinasti Publisher, 2021)
The unpreparedness of the cargo hold tank will result in losses for the company. To produce a truly clean loading space, it is necessary to carry out tank cleaning according to procedures, with adequate infrastructure, planning and good coordination between the parties concerned. The theoretical basis used in this paper describes the procedures for cleaning tanks on appropriate tankers, because delays will cause huge losses for the company. This research is qualitative in nature by conducting interviews and direct observations to see the process of Tank Cleaning activities on the ship so that the method used is a qualitative descriptive method. The type of research contained in the writing of this study is qualitative, namely research by collecting data on the MT ship. Success Marlina 33 then analyzes and draws conclusions in the form of explanations. Based on the results of research conducted at MT.